fNIRS Monitoring of Infant Prefrontal Cortex During Crawling and an Executive Functioning Task - Weibley, Hannah; Di Filippo, Mina; Liu, Xinran; Lazenby, Lillian; Goscha, Jackson; Ferreira, Alyssa; Muscalu, Laura; Rader, Nancy (Frontiers in Behavioral Neuroscience, 2021)
fNIRS is a brain-imaging technology used to reveal brain activity by measuring blood oxygenation. Using fNIRS we measured activity in the left prefrontal lobe of 8-14 month-old infants as they crawled or were pushed in a stroller and as they were given a passive attention task or an active executive function (EF) task. For each task, we measured peak total hemoglobin concentration and peak Oxy relative to baseline. Results revealed differences in peak Oxy levels for crawling vs. strolling and between the EF and passive cognitive tasks, with total hemoglobin greater for the EF task than the passive attention task. These results support the theoretical view that both active locomotion and EF engage the prefrontal cortex during early development.